2018
DOI: 10.33549/physiolres.933947
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Activation of Pro-Apoptotic Caspases With Autophagy in the Meckel´s Cartilage

Abstract: Mammalian Meckel´s cartilage is a temporary structure associated with mandible development. Notably, its elimination is not executed by apoptosis, and autophagy was suggested as the major mechanism. Simultaneous reports point to pro-apoptotic caspases as novel participants in autophagic pathways in general. The aim of this research was to find out whether activation of pro-apoptotic caspases (-2, -3, -6, -7, -8 and -9) was associated with autophagy of the Meckel´s cartilage chondrocytes. Active caspases were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…39 This pathway is associated with growth factor mediated processes 42 and FGF signaling was recently suggested as a regulator of bone growth through autophagy. 11 Caspase-8 is one of the key apoptotic components shown to be involved in autophagy 43 and is present also in nonapoptotic chondrocytes, 20 including the growth plate. 19 Inhibition of caspase-8 in micromass culture caused a 3-fold increase in Tnfsf10 (Trail) expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 This pathway is associated with growth factor mediated processes 42 and FGF signaling was recently suggested as a regulator of bone growth through autophagy. 11 Caspase-8 is one of the key apoptotic components shown to be involved in autophagy 43 and is present also in nonapoptotic chondrocytes, 20 including the growth plate. 19 Inhibition of caspase-8 in micromass culture caused a 3-fold increase in Tnfsf10 (Trail) expression.…”
Section: Discussionmentioning
confidence: 99%
“…17 Notably, activation of proapoptotic caspases was recently demonstrated to occur also in non-apoptotic growth plate chondrocytes, 19 and in developing Meckel's cartilage. 20 In keeping with this non-apoptotic role, caspase inhibition in vitro changed expression of osteogenic markers in developing chondrocytes. 19,21 This is in agreement with caspases having novel non-apoptotic roles in addition to their role in cell death.…”
Section: Introductionmentioning
confidence: 92%
“…However, in addition to their engagement in cell death ( Bohensky et al, 2014 ), autophagy has been identified also as a survival mechanism in MC ( Song et al, 2017 ; Luo et al, 2019 ). Notably, caspase-2 and -8 were found to be activated in the Beclin1 positive regions suggesting a role of these two regulators in autophagy ( Bilikova et al, 2019 ) and indicating that these pro-apoptotic caspases may be acting in a non-canonical manner in MC.…”
Section: The Removal Of the Intermediate Domain Of Meckel’s Cartilagementioning
confidence: 99%